Knowledge about human papillomavirus infection and cervical cancer prevention among nurses in Chiang Mai University Hospital, Thailand - Phianmongkhol Y. (2014)
This study was undertaken to evaluate knowledge about HPV infection and cervical cancer among nurses in Chiang Mai University Hospital, Thailand. The 16 questions evaluating knowledge were "true/false/do not know" type. Two hundred and twenty nurses agreed to participate in this survey. Most knew that cervical cancer is the most common female cancer in Thailand (92.7%), HPV infection is a causal factor of cervical cancer (81.8%), early stage cervical cancer is curable (94.1%), and an adequate scale of cervical screening could prevent morbidity and mortality from cervical cancer (86.8%). The majority of participants (more than 70%) correctly acknowledged risk factors for cervical cancer as smoking, having multiple sexual partners, and sex at an early age. However, the majority of participants did not know that HPV infection and early stage cervical cancer are commonly asymptomatic. In conclusion, knowledge regarding cervical cancer among nursing staff in the author's institute is considerably favorable. However, their understanding about the natural history of HPV infection and cervical cancer is suboptimal, and requires further attention if an effective cervical cancer screening program is to be implemented.